1990
DOI: 10.1007/bf00164004
|View full text |Cite
|
Sign up to set email alerts
|

Solitary and eusocial nests in a population of Augochlorella striata (Provancher) (Hymenoptera; Halictidae) at the northern edge of its range

Abstract: Augochlorella striata was studied at the northern limit of its range. The study population contained a mixture of solitary and social nest foundresses. Eusocial foundresses produced 1 or 2 workers before switching to a male biased brood. Solitary foundresses produced males first. Cells vacated by eclosed offspring were reused late in summer. A female biased brood resulted from cell reuse in both solitary and eusocial nests. Workers were slightly smaller than their mothers and were sterile although most of them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 14 publications
4
72
1
Order By: Relevance
“…Studies comparing populations of temperate halictine bees have shown that populations at higher altitudes (e.g., 2850 m, Eickwort et al 1996) tend to be solitary, while populations at lower elevations are social (Sakagami and Munukata 1972;. The same preclusion of sociality occurs in a halictine bee with regard to higher latitudes (Packer 1990), as expected based on biogeographic parallels between increasing altitude and increasing latitude in temperate zones (Merriam 1895). However, a subsequent phylogeographic study utilizing mitochondria!…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Studies comparing populations of temperate halictine bees have shown that populations at higher altitudes (e.g., 2850 m, Eickwort et al 1996) tend to be solitary, while populations at lower elevations are social (Sakagami and Munukata 1972;. The same preclusion of sociality occurs in a halictine bee with regard to higher latitudes (Packer 1990), as expected based on biogeographic parallels between increasing altitude and increasing latitude in temperate zones (Merriam 1895). However, a subsequent phylogeographic study utilizing mitochondria!…”
Section: Discussionmentioning
confidence: 73%
“…Extrinsic factors are increasingly thought to play a role in shaping the kinds of social behaviour expressed, and the trend for temperate social taxa to largely revert to solitary living at higher altitudes and latitudes is often cited in support of this claim (e.g., Sakagami and Munukata 1972;Packer 1990;Eickwort et al 1996;; but see Soucy and Danforth 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and breeding season length are among the most important factors influencing colony social variation, because almost all eusocial halictines must produce at least two broods per year, whereas solitary halictines need produce only one brood per year . Studies in several species of facultatively social Halictus and Lasioglossum indicate that colonies develop socially when foundresses can initiate nests early, but develop solitarily when nest initiation is delayed (Packer 1990, Yanega 1993, Hirata and Higashi 2008, Field et al 2012. Warmer soil temperatures can also speed up colony development, which can lead to production of more workers or extra worker broods (Weissel et al 2006, Hirata andHigashi 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The nesting biology and behav- (Eickwort et al 1996;Soucy and Danforth 2002;Soro et al 2010). While solitary and social populations of H. rubicundus may form phylogenetically separate lineages (Soucy and Danforth 2002) some halictines exhibit social polymorphism even within the same population (Packer 1990;Richards et al 2003;Hirata and Higashi 2008). While there are no known solitary H. farinosus populations, seasonal climatic differences might affect its sociality through the queen-worker size differential (Richards and Packer 1996).…”
Section: Comparisons To Other Halictus Speciesmentioning
confidence: 99%
“…In ground nesting bees the size of the food mass and the number that can be produced will depend on multiple environmental and biological factors including the size and activity levels of active foragers in the nest (Gathmann and Tscharntke 2002;Pereboom and Biesmeijer 2003) and the amount of available resources which, in turn, are highly dependent on weather and other environmental factors (Packer 1990;Minckley et al 1994;Richards and Packer 1996;Richards 2004). Repeat field studies of the same population can allow us to make comparisons between years to determine how weather patterns might affect phenology, productivity and sociobiology.…”
Section: Introductionmentioning
confidence: 99%